Arbuscular mycorrhizal fungal composition affects the growth and nutrient acquisition of two plants from a karst area - He, Yuejun; Jiang, Changhong; Yang, Hao; Wang, Yongjian; Zhong, Zhangcheng (Penerbit Universiti Kebangsaan Malaysia, 2017)
How the composition of the arbuscular mycorrhizal (AM) fungal community affects plant traits of different plant species in karst environments is poorly understood. Broussonetia papyrifera (a woody shrub) and Bidens pilosa (a herbaceous plant) growing in pots in limestone soil were inoculated with an AM fungus, either Funneliformis mosseae (FM), Diversispora versiformis (DV) or Glomus diaphanum (GD) or with an inoculum mixture of all three AM fungi (bn). B. papyrifera and B. pilosa seedlings inoculated with AM fungi showed a significant increase in biomass and nitrogen and phosphorus acquisition compared with the controls, which lacked mycorrhiza. Mixed fungal inoculations significantly enhanced biomass and nitrogen and phosphorus acquisition by B. papyrifera seedlings compared with single fungal inoculations. Nitrogen and phosphorus acquisition by B. papyrifera mycorrhizal seedlings was significantly greater than that of B. pilosa mycorrhizal seedlings. Fungal composition significantly influenced the mycorrhizal benefits of biomass and phosphorus acquisition and mixed fungal inoculations enhanced nitrogen acquisition. Plant species significantly affected nitrogen acquisition but did not have an effect on biomass and phosphorus benefits. We concluded that AM fungal associations increased plant growth and nutrient absorption and that in general a mixed inoculation of AM fungi enhanced biomass and nutrient acquisition more than a single AM fungal inoculation. In addition, a mycorrhizal association was more beneficial for B. papyrifera seedlings in terms of biomass and nutrient acquisition than for B. pilosa seedlings.